Cyanohydridoborate Anions: Synthesis, Salts, and Low‐Viscosity Ionic Liquids. Issue 14 (11th February 2019) - Bischoff, Lisa A.; Drisch, Michael; Kerpen, Christoph; Hennig, Philipp T.; Landmann, Johannes; Sprenger, Jan A. P.; Bertermann, Rüdiger; Grüne, Matthias; Yuan, Qinqin; Warneke, Jonas; Wang, Xue‐Bin; Ignat'ev, Nikolai V.; et al.
Abstract: High‐yield syntheses up to molar scales for salts of [BH(CN)3 ] − (2 ) and [BH2 (CN)2 ] − (3 ) starting from commercially available Na[BH4 ] (Na5 ), Na[BH3 (CN)] (Na4 ), BCl3, (CH3 )3 SiCN, and KCN were developed. Direct conversion of Na5 into K2 was accomplished with (CH3 )3 SiCN and (CH3 )3 SiCl as a catalyst in an autoclave. Alternatively, Na5 is converted into Na[BH{OC(O) R }3 ] ( R =alkyl) that is more reactive towards (CH3 )3 SiCN and thus provides an easy access to salts of2 . Some reaction intermediates were identified, for example, Na[BH(CN){OC(O)Et}2 ] (Na7 b ) and Na[BH(CN)2 {OC(O)Et}] (Na8 b ). A third entry to2 and3 uses ether adducts of BHCl2 or BH2 Cl such as the commercial 1, 4‐dioxane adducts that react with KCN and (CH3 )3 SiCN. Alkali metal salts of2 and3 are convenient starting materials for organic salts, especially for low viscosity ionic liquids (ILs). [EMIm]3 has the lowest viscosity and highest conductivity with 10.2 mPa s and 32.6 mS cm −1 at 20 °C known for non‐protic ILs. The ILs are thermally, chemically, and electrochemically robust. These properties are crucial for applications in electrochemical devices, for example, dye‐sensitized solar cells (Grätzel cells). Abstract : Mixed hydridocyanoborate room temperature ionic liquids with extraordinary low dynamic viscosities and high specific conductivities providing high thermal and electrochemical stabilities are presented.